¿Cómo analizar discursos de 140 caracteres? Propuesta metodológica para el estudio del discurso político de campaña en Twitter a partir del análisis estratégico con una perspectiva multimodal y crítica - Ventura, Aniela Suray (2018)
This article presents a methodology for the collection and analysis of corpus of political discourses published on Twitter. It has been drawn up in an ongoing doctoral research that seeks to report the persuasive discursive strategies used in the official accounts of the Argentine presidential candidates during the 2015 electoral campaign. This methodology is based on the strategic analysis of the discourse (Menéndez 2000, 2005, 2009, 2010, 2012) with a multimodal perspective (Kress & Van Leeuwen 2001). This expects, in the first place, the description of the corpus from a grammatical analysis with a functional systemic base (Halliday 1970, 1985, Halliday & Matthiessen 2014, Kress & Van Leeuwen 2001, Kress & Van Leuween 2006 [1996]) and pragmatic discursive studies (Lavandera 1992, Martin & White 2005, Sperber & Wilson 1994[1986]). And, secondly, the relation between the results obtained by these analysis in order to look for recurrences that allow to rebuild the produced discursive strategies. Finally, it seeks to achieve a critical analysis (Fairclough 2003) of these strategies, which allows to understand the campaign political discourse on Twitter in terms of discursive practices and analyze its influence on current political practices.